Interfacing Indigenous Knowledge and Climate Change Education - Sherpa, Pasang Dolma (Journal of Education and Research, 2017)
This paper is part of my PhD thesis. In this study, using the narrative inquiry methodology, lived experiences of schoolteachers who have been teaching the topics of climate change were collected mainly through interviews in Lamjung District. This paper reflects how teachers have been teaching climate change education and how they have been balancing indigenous knowledge to deal with climate change concerns. Generally teachers have been following implemented and experienced school curricula and accumulating the factual knowledge of climate change science, which has often been linked with the empirical interest of Habermas, especially, with his theory of knowledge and human interest in education. However, the stories of six schoolteachers were not limited to what they have been teaching but also how they have been teaching, how they have been linking environmental concerns with the indigenous knowledge and cultural practices that have been contributing to sustainable management of the natural resources and climate change resilience. Thus the stories of the teachers were also analysed through Habermas’s practical and emancipatory interests and indigenous worldviews by reflecting on my own stories while working on the theme of climate change and indigenous peoples at community, national and global levels since 2009.